Regulating Noncovalent Interactions in Amino‐Amide–Copper Complexes. Issue 12 (30th March 2018) - Lechuga‐Islas, Víctor; Tlahuext, Hugo; Falcón‐León, Martha P.; Sánchez‐De Jesús, Félix; Moo‐Puc, Rosa E.; Chale‐Dzul, Juan B.; Tapia‐Benavides, Antonio R.; Tlahuextl, Margarita
Abstract : The relevance of intermolecular noncovalent Cl··· Cu interactions in the magnetic and biological behavior of copper complexes derived from amino amides is studied. Crystallography studies show that these complexes tend to stack, favoring noncovalent interactions (hydrogen bonding and Cu··· Cl). However, the presence of substituents at the C10 and C13 positions regulates the supramolecular structures in2 . Thus, magnetic studies at 93, 293, and 353 K demonstrate that magnetic exchange is favored only by Cu–Cl··· Cu interactions. Moreover, biological studies show that only those copper complexes with ferromagnetic behavior present cytotoxic activity. Natural bond orbital (NBO) and quantum theory of atoms in molecules (QTAIM) computations are used to corroborate the presence of the noncovalent interactions. Abstract : Copper complexes derived from amino amides tend to stack, favoring noncovalent interactions. However, intermolecular noncovalent Cl··· Cu interactions determine the magnetic behavior and potentially the biological activity of these compounds.